Inducible biosynthesis and immune function of the systemic acquired resistance inducer N-hydroxypipecolic acid in monocotyledonous and dicotyledonous plants. (6th July 2020) - Schnake, Anika; Hartmann, Michael; Schreiber, Stefan; Malik, Jana; Brahmann, Lisa; Yildiz, Ipek; von Dahlen, Janina; Rose, Laura E; Schaffrath, Ulrich; Zeier, Jürgen
Abstract : N -hydroxypipecolic acid, which systemically accumulates in phloem sap of Pseudomonas syringae -inoculated cucumber, is synthesized and functions as an activator of systemic acquired resistance in diverse monocotyledonous and dicotyledonous plant species. Abstract: Recent work has provided evidence for the occurrence of N -hydroxypipecolic acid (NHP) in Arabidopsis thaliana, characterized its pathogen-inducible biosynthesis by a three-step metabolic sequence from l -lysine, and established a central role for NHP in the regulation of systemic acquired resistance. Here, we show that NHP is biosynthesized in several other plant species in response to microbial attack, generally together with its direct metabolic precursor pipecolic acid and the phenolic immune signal salicylic acid. For example, NHP accumulates locally in inoculated leaves and systemically in distant leaves of cucumber in response to Pseudomonas syringae attack, in Pseudomonas -challenged tobacco and soybean leaves, in tomato inoculated with the oomycete Phytophthora infestans, in leaves of the monocot Brachypodium distachyon infected with bacterial ( Xanthomonas translucens ) and fungal ( Magnaporthe oryzae ) pathogens, and in M. oryzae -inoculated barley. Notably, resistance assays indicate that NHP acts as a potent inducer of acquired resistance to bacterial and fungal infection in distinct monocotyledonous and dicotyledonous species. Pronounced systemic accumulation of NHP in leaf phloem sap of locally inoculated cucumber supports a function for NHP as a phloem-mobile immune signal. Our study thus generalizes the existence and function of an NHP resistance pathway in plant systemic acquired resistance.